2020
DOI: 10.46961/jip.v8i2.159
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF e-WOM AND BRAND LOVE ON THE PURCHASING DECISIONS IN ONLINE SHOPPING

Abstract: The objectives of this research are: to analyze the effect of e-WOM on brand love, to analyze the effect of e-WOM on purchasing decisions in online shopping, to analyze the effect of brand love on purchasing decisions in online shopping. This research used quantitative methods, with a total sample of 243 online shopping in the Jabodetabek area. The research used online survey methods in the form of questionnaires. The sampling technique used purposive sampling. The scaling technique of the study applied Likert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…As the consumer's love for a brand increases, it influences their purchase decisions. Research conducted by Rahayu (2020) has shown that brand love positively contributes to purchase decisions. This indicates that when consumers like or love a particular brand, it influences their product selection process.…”
Section: The Influence Of Brand Love On Purchase Decisionmentioning
confidence: 99%
“…As the consumer's love for a brand increases, it influences their purchase decisions. Research conducted by Rahayu (2020) has shown that brand love positively contributes to purchase decisions. This indicates that when consumers like or love a particular brand, it influences their product selection process.…”
Section: The Influence Of Brand Love On Purchase Decisionmentioning
confidence: 99%